Influence of platelet γ-glutamyltransferase on oxidative stress and apoptosis in the presence of holo-transferrin - (:unkn) unknown (My University, 2012)
Several studies have documented that formation of oxidant mediators may induce apoptosis in nucleated and anucleated cells by modulating intracellular signalling pathways. Reactive oxygen species (ROS) play a very important role in the platelet function. γ-Glutamyltransferase (GGT), a novel source of cellular production of oxidants in the presence of iron and reduced glutathione (GSH), is also found on platelets. The role of platelet-bound GGT in platelet apoptosis and oxidative stress is unknown. The aim of our study was to determine the effects of platelet GGT activity on oxidative stress and apoptotic events in vitro via determination of lipid peroxidation (LPO), protein oxidation, GSH, catalase, caspase-3 activation and phosphatidylserine (PS) exposure in the presence of holo-transferrin (Tf). Stimulation of platelet GGT activity with GSH and glycylglycine (GlyGly) increased caspase-3 activation and PS exposure. A significant increase in lipid and protein oxidation and decrease in GSH and catalase levels was also observed in platelets with stimulation of GGT activity in the presence of Tf. Inhibition of GGT activity effectively reduced all the markers. These results suggest that generation of ROS by the GGT/GSH/Tf system can modify the platelets' redox environment and induce apoptosis in in vitro conditions.
Keywords: Female; Humans; Male; Sulfhydryl Compounds; Glutathione; Lipid Peroxidation; Oxidative Stress; Apoptosis; Caspase 3; Catalase; Protein Carbonylation; Reactive Oxygen Species; gamma-Glutamyltransferase; Enzyme Inhibitors; Blood Platelets; Dipeptides; Extracellular Space; Phosphatidylserines; Transferrin